Aalmarkierungen in der Eider und im Gebiet der Deutschen Bucht - Aker, A.; Koops, H. (1969)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010